Challenges in risk analysis for science and engineering : development of a common language - Temple, Tracey J.; Ladyman, Melissa K. (IOP (Series). Release 22., 2022)
The aim of this reference text is to provide a common language and consistent approach to risk assessment across science and engineering disciplines through the collation of detailed, real examples and scenarios. Examples are drawn from a variety of industries and cover key risk topics such as tolerability, data collection, hazard identification and hazard interpretation. The approaches communicate common challenges and are compared and contrasted, with a particular focus on the terminology used. The book is essential reading for scientists and engineers that undertake risk assessment, including industry practitioners, researchers in academia and those with a general interest in improving risk assessment processes. It is also a valuable reference for science and engineering students that regularly undertake risk assessments or study courses on risk assessment.